Continued Warfarin Better than Heparin Bridging during Device Implantation - Nichols, Emma Hitt (MD Conference Express, 2013)
Importantly, up to 35% of patients that undergo arrhythmic device implantation also require chronic anticoagulant treatment. Current clinical practice guidelines recommend discontinuing warfarin treatment prior to surgery and treating patients with low-molecular-weight heparin [Douketis JD et al. Chest 2012]. This article presents data from the Bridge or Continue Coumadin for Device Surgery Randomized Controlled Trial [BRUISE CONTROL; Birnie D et al. N Engl J Med 2013], which tested the hypothesis that continued treatment with warfarin would reduce the number of device-pocket hematomas without increasing the risk of major perioperative bleeding events.